Altered aortic arch geometry in patients with type B aortic dissection. (17th April 2020) - Cao, Long; Lu, Weihang; Ge, Yangyang; Wang, Xinhao; He, Yuan; Sun, Guoyi; Liu, Jie; Liu, Xiaoping; Jia, Xin; Xiong, Jiang; Ma, Xiaohui; Zhang, Hongpeng; et al.
Abstract: OBJECTIVES: This study aims to evaluate differences in proximal aorta geometry and identify specific anatomical predictors of type B aortic dissection (TBAD). METHODS: We evaluated computed tomographic angiograms of controls ( n  = 185) and patients with acute TBAD ( n  = 173). Using propensity score matching, we created 2 groups of 127 patients. 3mensio Vascular software was used to analyse the computed tomographic angiograms and measure the diameter, length, tortuosity index and angulation of the proximal aorta (divided into ascending aorta and aortic arch). Tortuosity index was calculated by dividing the centre lumen line length of the aortic segment by its shortest length. Angulation was measured by the centre lumen line 'tangent line angle'. Two independent multivariable models identified significant anatomical associations regarding the tortuosity and angulation geometry. RESULTS: Aortic diameter and ascending aorta and aortic arch lengths in TBAD increased significantly. The aortic arch tortuosity was significantly higher in the TBAD group ( P  < 0.001), with no difference regarding the ascending aorta ( P  = 0.11). Ascending aorta and aortic arch angulation were significantly higher in the TBAD group ( P  = 0.01, P  < 0.001, respectively). Multivariable analyses showed that increased aortic arch tortuosity and angulation were significant predictors of the development of TBAD [odds ratio (OR) 1.91, 95% confidence interval (CI) 1.40–2.59; P  < 0.001 and OR 1.08, 95% CI 1.04–1.12; P  < 0.001], respectively. CONCLUSIONS: In addition to proximal aorta dilation and elongation, we identified increased aortic arch tortuosity and angulation as possible specific predictors of TBAD.